Digestibility of different wheat products in white shrimp Litopenaeus vannamei juveniles - Nieto López, Martha Guadalupe; Tapia Salazar, Mireya; Ricque Marie, Denis; Villarreal Cavazos, David Alonso; Lemme, Andreas; Cruz Suárez, Lucía Elizabeth (Elsevier Science Pub, 2011)
Dry matter, energy, crude protein and amino acid apparent digestibility coefficients (ADCs) were determined in white shrimp juveniles for six wheat products: hard red winter whole grain meal (HWG), Rayon whole grain meal (RWG), Durum whole grain meal (DWG), hard red winter clear flour (HCF), mixed wheat 2nd clear flour (MCF) and semolina (S). The test diets included 30% of the test ingredients and 70% of a ground commercial diet supplemented with 1% chromic oxide and 1% sodium alginate. Amino acid contents in the ingredients, diets and feces were analyzed, and digestibility was determined by difference in order to minimize the impact of endogenous amino acid losses; crude protein and amino acids ADCswere adjusted for dietary preprandial losses in seawater. In general, nutrients digestibility was far higher in the wheat products than in the fish meal-based reference diet. Drymatter and crude proteinADCswere not statistically different amongwheat products (from84 to 96% and from88 to 107% respectively). Energy ADCs were significantly higher for clear flours (96% for HCF and MCF) than forwhole grainmeals and S (from83 to 86%). Total amino acids (TAA) and essentialamino acids (EAA) ADCs, once adjusted for preprandial leaching fromthe experimental diets, ranged from81 to 89% and from 58 to 81% respectively, and were statistically comparable among wheat products. Low Thr ADCs appear as a common feature of the amino acids digestibility profiles for whole grain meals, clear flours, or semolina.